2004
DOI: 10.1256/qj.03.40
|View full text |Cite
|
Sign up to set email alerts
|

A canopy model of mean winds through urban areas

Abstract: SUMMARYAn urban canopy model is developed for spatially averaged mean winds within and above urban areas. The urban roughness elements are represented as a canopy-element drag carefully formulated in terms of morphological parameters of the building arrays and a mean sectional drag coefficient for a single building. Turbulent stresses are represented using a mixing-length model, with a mixing length that depends upon the density of the canopy and distance from the ground, which captures processes known to occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
254
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(270 citation statements)
references
References 27 publications
10
254
3
3
Order By: Relevance
“…The roughness length results, in figure 8(a), closely follow the skin friction trends as a function of both the solidities, as shown in table 1. The drag-peak location herein is partially in contrast with previous studies, for which it was found at λ P ≡ λ F ≈ 0.15 (Hagishima et al 2009;Leonardi & Castro 2010;Kanda et al 2004) and λ P ≡ λ F ≈ 0.16 (Santiago et al 2008;Coceal & Belcher 2004). These differences are perhaps not surprising giving the high uncertainty in the fitting procedure which results in the visible scatter of the data for different studies in figure 8(a), even when values of similar frontal and plan solidity are considered.…”
Section: Effect Of Surface Morphology On Aerodynamic Parameterscontrasting
confidence: 99%
See 1 more Smart Citation
“…The roughness length results, in figure 8(a), closely follow the skin friction trends as a function of both the solidities, as shown in table 1. The drag-peak location herein is partially in contrast with previous studies, for which it was found at λ P ≡ λ F ≈ 0.15 (Hagishima et al 2009;Leonardi & Castro 2010;Kanda et al 2004) and λ P ≡ λ F ≈ 0.16 (Santiago et al 2008;Coceal & Belcher 2004). These differences are perhaps not surprising giving the high uncertainty in the fitting procedure which results in the visible scatter of the data for different studies in figure 8(a), even when values of similar frontal and plan solidity are considered.…”
Section: Effect Of Surface Morphology On Aerodynamic Parameterscontrasting
confidence: 99%
“…These studies include both numerical and physical experiments (Cheng & Castro 2002b;Coceal & Belcher 2004;Kanda et al 2004;Cheng et al 2007;Hagishima et al 2009;Santiago et al 2008;Leonardi & Castro 2010 among various others). Open symbols in figure 2(a) show the cases examined in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…These two parameters are now removed and the attenuation coefficient is derived from an urban morphology relation (Table II, Eq. 21) using available parameters (Coceal and Belcher, 2004;Di Sabatino et al, 2008).…”
Section: The Single-layer Urban Canopy Model In Wrfmentioning
confidence: 99%
“…They have led to the development of the few urban canopy models that are available today. These models usually assume spatially averaged velocity profiles, adopting an approach similar to that used for flow over vegetation canopies (Finnigan, 2000;Coceal and Belcher, 2004), and, in some cases, even a single spatially averaged canopy velocity (U C , see Bentham and Britter, 2003). These properties depend strongly on the local geometry and existing models generally relate them to the mean building height (H b ) and the lambda parameters (λ p , and λ f , see above).…”
Section: Introductionmentioning
confidence: 99%